Valley-filling instability and critical magnetic field for interaction-enhanced Zeeman response in doped WSe2 monolayers (vol 7, 198, 2021) - Xuan, Fengyuan (NATURE PORTFOLIO, 2022)
10.1038/s41524-021-00690-7